Faktory složnosti sochranenija ravnovesija s broskom predmeta v chudožestvennoj gimnastik - Medvedeva, E. N.; Terekhina, R. N.; Kryuchek, E. S.; Davydova, T. Yu.; Davydova, A. Yu.; Kolesnikova, T. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
High-quality and effective performance of balances by gymnasts, including throwing objects, makes the competitive composition more spectacular and increases its technical value. However, at the moment, the lack of an objective approach to assessing the complexity of these elements makes it difficult not only to assess the technical skills of gymnasts, but also to consistently and logically master the entire variety of equilibria. This article presents the results of research that allowed to specify the factors that determine the complexity, and therefore the technical value of equilibria with throws of objects in rhythmic gymnastics.